Colostrum Composition, Characteristics and Management for Buffalo Calves: A Review - Daria Lotito; Eleonora Pacifico; Sara Matuozzo; Nadia Musco; Piera Iommelli; Fabio Zicarelli; Raffaella Tudisco; Federico Infascelli; Pietro Lombardi (Veterinary Sciences, 2023)
In this review, the composition, characteristics, and management of dairy buffalo calves were examined and compared with bovines. The neonatal period is critical for buffalo calves and is characterized by a high mortality rate (more than 40%). The early intake of high-quality colostrum (IgG > 50 mg/mL) is the one way to improve the immune system of calves (serum IgG > 10 mg/mL after 12 h), thus increasing their chances of survival. Mainly in intensive farms, the availability of high-quality colostrum is necessary; thus, good quality colostrum is often stored to provide newborn calves which cannot be fed by their mothers. Also, the manipulation of the immunological status of animals through vaccination has been depicted since the quality of colostrum tended to be influenced by vaccination against pathogens. Buffalo breeding is constantly expanding in Italy, mainly thanks to the Mozzarella cheese production that represents the excellence of the “Made in Italy” and is exported worldwide. Indeed, high calf mortality rates directly affect the profitability of the business. For these reasons, the aim of this review was to examine specific research on buffalo colostrum that, compared with other species, are scarce. Improving the knowledge of buffalo colostrum, in terms of characteristics and management, is critical to guarantee buffalo newborns’ health in order to reduce their mortality rate. Importantly, considering the knowledge on cattle valid also for buffalo is a widespread, and often erroneous, habit in several fields, including colostrum feeding. Therefore, the two species were compared in this review.